Fundamental frequency, intensity, and vowel selection: effects on measures of phonatory stability - Gelfer, M P (Journal of speech and hearing research, 1995)
Measures of phonatory stability such as jitter, shimmer, and signal-to-noise ratio (SNR) are increasingly used in clinics and laboratories, yet questions about the effects of various aspects of voice production on these acoustic variables have received only limited attention. The purpose of the present study was to examine the effects of frequency, intensity, and vowel selection on those measures of phonatory stability. Twenty-nine young adult females were used as subjects. Each subject produced vocalizations at her speaking fundamental frequency (SFF) and one octave above SFF; at 60, 70, and 80 dB; and on the vowels /i/ and /a/, for a total of 12 vocalizations per subject. These vocalizations were then analyzed, using CSpeech acoustic analysis software, to obtain measures of jitter, shimmer, and SNR. Results revealed that frequency, intensity, and vowel selection all affected various phonatory stability measures, with the highest perturbation values almost always occurring in the low frequency-low intensity condition. Implications and physiological explanations for the results of the study were presented.